EVENT HISTORY ANALYSIS (EHA) METHOD AS EVENT STUDY DEVELOPMENT - Sri Suryaningsum; Prasetya, Fikri Dwi (Count : Journal of Accounting, Business and Management, 2024)
This study aims to introduce event history analysis (EHA) as an alternative to event study in accounting, business, and economics research, especially for events that span a long time. Event Studies are generally limited to analysing daily events, whereas many phenomena in this area, such as post-IPO stock price stabilization, require long-term analysis. Event History Analysis, which originated in medicine, has evolved and began to be used in business research in Western countries. However, its use in Indonesia is still limited. Inappropriate use of Event Studies for long-term events may lead to biased research results. The method used in this study is an in-depth comparative literature analysis between Event Study and Event History Analysis. In addition, data testing simulations were carried out using Event History Analysis. The results of this study present a comprehensive comparison table between Event Study and Event History Analysis. Practical guidance on data preparation for COX regression analysis (one of the EHA methods) is also provided. This study also provides examples of research titles relevant to EHA, complete with event identification, independent variables, and expected interpretations. This study contributes to increasing the validity and accuracy of analyses in studies involving a relatively long time span.